Reconocimiento de patrones en imágenes de video para el monitoreo de eventos de tráfico vehicular en Santiago de Cali (2018)
In this project, the design of a distributed system for patterns recognition in video images is made, focused mainly on patterns that negatively impact vehicular traffic in the city of Santiago de Cali. First, the identification of the patterns or behaviors that suppose a greater impact on the vehicular traffic of the city was made. Based on these patterns, a cluster was built based on infrastructure technologies of distributed systems for data analysis, an algorithm was implemented for the recognition of the selected patterns, and handling the mechanisms for the notification of corresponding alerts. After, a test plan was elaborated with each one of the different possible configurations, in order to determine the performance at the moment of processing the video images. Finally, an analysis is made based on the results which will serve as base for future research